Implikasi Perubahan Iklim terhadap Produktivitas Pangan di Desa Mandalawangi Tahun 2025 - Ajeng Roro Syanti; Ratu Majidah Qonitah; Inashaqi Salamah; Alifah Azahra Yamin; Wahyu Kartiko Utami (Journal of Creative Student Research, 2026)
Climate change, characterized by the increasing frequency and intensity of hydrometeorological disasters, has become a serious threat to the agricultural sector and food security in Indonesia. Pandeglang Regency, particularly Mandalawangi Village, is one of the areas significantly impacted by floods and extreme weather, disrupting food productivity and the socio-economic conditions of the community. This study aims to analyze the implications of climate change on food productivity and identify community adaptation strategies for maintaining livelihoods amidst increasing disaster risk. The study employed qualitative methods with a single instrumental case study approach. Data were obtained through interviews, observation, and documentation, then analyzed using data reduction techniques, data presentation, and conclusion drawing using source triangulation. The results indicate that climate change triggers increased extreme rainfall, leading to flooding, agricultural land damage, disruption of the planting calendar, increased pest infestation, and decreased rice productivity. Nevertheless, food availability in Mandalawangi Village can still be maintained through commodity diversification, utilization of upland rice, distribution of superior seeds, development of irrigation infrastructure, and various forms of government transfers. These findings emphasize the importance of strengthening farmers' adaptive capacity and agricultural policies responsive to climate change to maintain sustainable food production and the well-being of rural communities.